Implementasi Program Outbound dalam Membentuk Karakter Percaya Diri Siswa - Amiladini Nurmaulida; Oki Suprianto; Firman Robiansyah (Universitas Muhammadiyah Mataram, 2025)
Abstract: This article aims to describe the implementation of various outbound program activities at SD Peradaban Serang in forming the self-confidence character of grade 4 students. This study discusses the importance of students having high self-confidence so that students can apply the knowledge and skills they have gained in developing their own interests, talents and skills/capabilities maturely. However, in reality, the function of education as a means of forming student character has not been fully implemented or has not been optimally applied in the educational environment itself. This study uses a qualitative approach with a case study method, data were collected through observation, interviews, and documentation studies. The results of the study showed that the outbound program consisting of flying fox activities, fun games, and life skills was able to foster six indicators of self-confidence character, namely: confident in one's own abilities, optimistic, responsible, rational, brave, and objective. Overall, of the 17 students observed, most of them received the highest assessment reaching 4.5. with the predicate